SANKSI HUKUM TERHADAP ADVOKAT YANG MELANGSUNGKAN TINDAK PIDANA PEMALSUAN DOKUMEN KLIEN DI PENGADILAN - Muhammad Khairil Agum; Nur Rahmanto Hariyad (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: An advocate or often called a lawyer is a job that is untouchable, independent, responsible for a fair, honest and safe trial of every judge when defending law, justice, truth and human rights. This research was conducted with the type of normative legal method and based on the Act. The results of the study show that acts that violate falsifying letters and documents specified in Article 263 of the Criminal Code are subject to punishment for a maximum period of 6 years. And a lawyer is freed from his obligation to practice under the provisions of Article 10 of Law No. 13 of 2003 concerning lawyers who are carried out by lawyers' organizations that do not have the right to practiceKeywords: Law; Advocate; Forgery of Documents Abstrak: Advokat atau sering disebut pengacara ialah pekerjaan yang tidak tersentuh, independen, bertanggungjawab atas pengadilan yang adil, jujur serta aman secara peradilan terhadap setiap hakim saat membela hukum, keadilan, kebenaran serta HAM. Penelitian ini dilakukan dengan jenis metode hukum normative dan berdasarkan UU. Hasil penelitian menunjukkan bahwa tindakan yang melanggar memalsukan surat dan dokumen yang ditentukan pada Pasal 263 KUHP terancam hukuman dalam kurunwaktu selama-lamanya 6 tahun. Dan seorang pengacara dibebaskan dari kewajibannya untuk berpraktik berdasarkan ketentuan Pasal 10 UU No.13 Tahun 2003 mengenai pengacara yang dilakukan oleh organisasi pengacara yang tidak memiliki hak untuk berpraktikKata kunci: Hukum; Advokat; Pemalsuan Dokumen